Planlægningens (oversete) årti. Argumenter for adgangsbegrænsning i 1970’erne - Hansen, Else (Historisk Tidsskrift, 2018)
An overlooked decade of planning. Reasons for restricted admission to Danish universities in the 1970s Restricted admission to Danish universities was introduced in 1976-77. This political initiative was meant to ensure an appropriate number of students, both overall and in terms of employment opportunities. Restricted admission was discussed already in the 1930s, proposed by the universities as a means to improve the quality of the student body. In the 1960s, restricted admission was politically unacceptable because it went against welfare state ideals of ensuring everyone the education he or she had the desire and ability to pursue. The political atmosphere of the 1970s supported the notion that public spending should be limited and universities not educate for unemployment. Restricted admission was primarily based on grade averages from the admissions exam, yet even the possibility of supplementing exam results with work experience was introduced. The universities lost their representation in the ministry’s committees because of a new administrative structure. They now pointed out, in vain, that restricted admission would not result in ‘better’ students. Student organizations disavowed it in any form. In a broader perspective, access limitation was designed with elements from welfare state ideals side by side with initiatives that, in the following decades, were linked with New Public Management and later with the so-called competition state.